Strategi Manajemen Pendidikan Islam Luar Sekolah dalam Menghadapi Tantangan Era Digital - Retno Saptowuri Astuti; Firmansyah Firmansyah (Eduvis : Jurnal Manajemen Pendidikan Islam, 2025)
Islamic education outside schools has a strategic role in shaping the character and religious values of the community that are not reached by formal education. This research aims to describe the meaning and characteristics of out-of-school Islamic education, the concept and principles of management in out-of-school Islamic education, as well as the challenges and solutions in managing out-of-school Islamic education in the modern era. This research uses a qualitative approach with a descriptive method through library research. Data was collected from various relevant scientific literature sources, then analyzed using content analysis techniques. The results of the study show that Islamic education outside of school is a flexible, community-based, and prioritizes aspects of spirituality in daily life. The forms of institutions include the Al-Qur'an Education Park (TPQ), taklim councils, flash Islamic boarding schools, and community da'wah institutions. The management of Islamic education outside schools emphasizes the principles of community participation, local wisdom, transparency, and spirituality-based. The implementation of management functions includes planning based on community needs, flexible organization, contextual implementation, and continuous evaluation. Leadership in this institution is spiritual and servant leadership. The main challenges faced include limited human resources, lack of operational funds, lack of government regulation and supervision, low interest in the younger generation, and stigma and marginalization. Solutions that can be applied include mapping community needs, empowering local educators, diversifying learning programs, and utilizing digital technology. Technology plays a vital role in supporting the effectiveness of Islamic education outside of school through online learning platforms, social media, Islamic applications, and interactive materials. This study concludes that good management, visionary leadership, active community participation, and technological innovation are the keys to the success of Islamic education outside schools in responding to the challenges of the times while maintaining Islamic values.